2012
DOI: 10.1097/brs.0b013e31821eb295
|View full text |Cite
|
Sign up to set email alerts
|

Could Junctional Problems at the End of a Long Construct be Addressed by Providing a Graduated Reduction in Stiffness?

Abstract: Reduction of hypermobility caused by extended arthrodesis may represent a new and ideally suited function for PDS devices. Mechanically, the devices were seen to kinematically restore abnormal distal motion, especially with placement of the PDS at the thoracolumbar junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…10 In contrast to the results of Mageswaran et al, Durani et al reported that a dynamic stabilization system could reduce the hypermobility caused by extended arthrodesis. 11 In addition, other study assessed the intradiscal pressure (IDP) in monosegmental fusion at L5-S1 and hybrid surgery (Dynesys at L4-5 and rigid fixation at L5-S1). 12 The IDP at the segment adjacent to the fusion was reduced when a dynamic stabilization system was added above the segment that underwent fusion.…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast to the results of Mageswaran et al, Durani et al reported that a dynamic stabilization system could reduce the hypermobility caused by extended arthrodesis. 11 In addition, other study assessed the intradiscal pressure (IDP) in monosegmental fusion at L5-S1 and hybrid surgery (Dynesys at L4-5 and rigid fixation at L5-S1). 12 The IDP at the segment adjacent to the fusion was reduced when a dynamic stabilization system was added above the segment that underwent fusion.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Similarly, Durrani et al reported that the use of posterior dynamic stabilization at the caudal-most level reduces the adjacent-level hypermobility and the potential for distal junctional kyphosis. 17 Less-restrictive hook instrumentation has also been shown to reduce the risk of PJK clinically 3 10 15 18 ; however, in vitro studies demonstrating their mechanical advantage in the thoracic spine is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective review of a multicenter database, rod fracture occurred in 15 % of patients [ 31 ]. The high stiffness of conventional metal rods creates compliance mismatches between spine and instrumentation, stress concentrations, and motion redistribution, factors which likely contribute to rod breakage, screw pull-out, auto-fusion, and junctional kyphosis [ 15 , 32 , 33 ]. Using a computational model, a more flexible non-fusion correction system for AIS which used non-locking polyaxial pedicle screws and mobile connectors was reported to reduce intervertebral rotation less than more rigid implants [ 34 ].…”
Section: Introductionmentioning
confidence: 99%